Strengthening sustainable food systems through agri-tech startups: a fuzzy DEMATEL analysis of critical success factors - Sharma, Manu; Gupta, Priyanka; Joshi, Sudhanshu (Frontiers in Sustainable Food Systems, 2025)
IntroductionTransforming agri-food systems toward sustainability and responsible production is essential for achieving Sustainable Development Goal 12, particularly in developing countries. Agri-tech startups play a pivotal role as catalysts of innovation, leveraging technology and novel business strategies to reduce waste, enhance product visibility, and address challenges across the agricultural supply chain.MethodsThis study aims to identify and characterize the critical success factors (CSFs) that influence the effectiveness of agri-tech startups in enabling sustainable agri-food supply chains. Using a Multi-Criteria Decision-Making (MCDM) approach grounded in the Technology-Organization-Environment (T-O-E) framework, 25 CSFs were extracted and analyzed from the existing literature.ResultsThe analysis highlights the most influential CSFs within the cause group, including policy coordination, rural ecosystem readiness, and innovation capacity. These factors collectively determine the capability of startups to scale operations while addressing environmental and operational challenges.DiscussionFindings demonstrate how local alternative food networks can serve community interests while meeting global sustainability challenges. The study provides practical guidance for assessing startup readiness and scalability and contributes theoretical insights into the integration of technological, organizational, and environmental factors in sustainable agri-food systems.